Why Do French Engineers Find Stable Jobs Faster than PhDs? - David N. Margolis; Luis Miotti (Institute of Labor Economics (IZA), 2017)
This paper studies why PhDs in France take longer to find stable jobs than engineers. Using data from CEREQ's "Génération 2004" survey, we show that job finding rates of PhDs are lower than those of engineers and document the differences in their observable characteristics and fields of study. We show that this phenomenon is due to multiple factors: heterogeneity in student characteristics along observable (but not unobservable) dimensions and fields of study, directed search toward public sector positions (especially professors) among PhDs and reservation wages of PhDs for private sector jobs that are "too high" relative to their value of marginal product.
Keywords: J24; I23; J64; 330; school-to-work transition; STEM; directed search; wage subsidies